ANALISIS RASIO KEUANGAN PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH: (Studi Kasus pada Pemerintah Kabupaten Magelang Tahun Anggaran 2018-2020) - Nuzul Nikmatul Ula; Risma Wira Bharata (Transpublika Publisher, 2022)
This study aims to assess the financial performance of the Magelang Regency government using financial ratio analysis based on the Realization Report of the Magelang Regency Regional Revenue and Expenditure Budget for the 2018-2020 Fiscal Year. The data collection method used is documentary. In the analytical approach, a quantitative approach is used by calculating the Regional Financial Independence Index, PAD Performance Index and Regional Financial Performance Index. Based on the results of measurements and analyses of regional financial performance, it is possible to conclude that the Magelang Government's independence in terms of financial capabilities remains very low in order to meet the region's, government's, development, and social development needs. As a result, Magelang Regency's level of effectiveness and efficiency in regional financial management is classified as less effective. The Magelang Regency Spending Efficiency Ratio for 2018-2020 demonstrates that the Magelang Regency Government is perceived to have squandered its budget.